Analisis Pengaruh Pendapatan Asli Daerah (PAD) dan Dana Alokasi Umum (DAU) Terhadap Produk Domestik Regional Bruto (PDRB) di Provinsi Papua Barat 2014-2018 (Studi Kasus 10 Kabupaten dan 1 Kota) - Gabriel Sasea; Rully N Wurarah; Muhammad Guzali Tafalas (Fakultas Ekonomi dan Bisnis, Universitas Papua, 2020)
This study aims to analyze the effect of Regional Original Revenue and General Allocation Funds on Gross Regional Domestic Product. The method used in this research is quantitative descriptive analysis techniques using time series data for 2014-2018 and using